Postponing the production of ant domatia as a strategy promoting an escape from flooding in an Amazonian myrmecophyte - Izzo, Thiago Junqueira (2018)
Background and Aims: Even when adapted to flooding environments, the spatial distribution, growing strategies and anti-herbivore defences of plants face stressful conditions. Here we describe the effects of flooding on carbon allocation on growth, domatia and leaf production, and the herbivory on the myrmecophyte domatia-bearing Tococa coronata Benth. (Melastomataceae) growing along river banks in the Amazon region. Methods: In an area of 80 000 m2 of riparian forest along the Juruena River we actively searched for individuals of T. coronata. In each plant we evaluated the size of the plant when producing the first domatium and determined its best predictor: (1) plant total height; (2) size of plants above flood level; or (3) length of time each plant spent underwater. We also compared the herbivory, internode elongation, foliar asymmetry and specific leaf weight between T. coronata individuals growing above and below the maximum flooding level. The distance to the river and the height of the first domatium produced were compared between T. coronata and its sympatric congener, T. bulifera. Key Results: We found that T. coronata invests in rapid growth in the early ontogenetic stages through an elongation of internodes rather than in constitutive anti-herbivore defences to leaves or domatia to exceed the maximum flooding level. Consequently, its leaf herbivory was higher when compared with those produced above the flooding level. Individuals with leaves above flood levels produce coriaceous leaves and ant-domatias. Thus, flooding seems to trigger changes in growth strategies of the species. Furthermore, T. coronata occurs within the flood level, whereas its congener T. bullifera invariably occurs at sites unreachable by floods. Conclusion: Even in conditions of high stress, T. coronata presents both physiological and adaptive strategies that allow for colonization and establishment within flooded regions. These mechanisms involve an extreme trade-off of postponing adult plant characteristics to rapid growth to escape flooding while minimizing carbon allocation to defence.